Finite element analysis and experiemental verification of polymer melt temperature and product shrinkage in injection molding / Gan Teck Wan - Gan, Teck Wan (2012)
It is not an easy task to control the final properties of the plastic product since there is a lot factors like mold design, processing parameters and behavior of the plastic material during injection molding have to be taken into consideration. Due to these factors, injection molded plastic part varies accordingly with the parameter setting and results in different dimensional variation from part to part. For better quality control, the effect of these processing parameters on shrinkage must be known before manufacturing. In this study, finite element analysis was used to determine this effect by using one-way interaction approach and two-way interaction approach. In one-way interaction approach, three finite element analysis tools namely computational fluid dynamic, transient thermal analysis and static structural analysis were used to model the mold filling, mold cooling and product shrinkage after ejection as separate process. In the two-way interaction approach, a highly intelligent multi-physics architecture composed of both computational fluid dynamic and finite element analysis tools were proposed to study the injection molding shrinkage problem as a single process. Two test mold cavities namely mold cavity-I and mold cavity-II were used in this study. Marlex HDPE 9500 was injection molded in mold cavity-I and TOYOLAC 250 ABS was injection molded in mold cavity-II. Both cavities product shape were respectively rectangular in geometry with dimension of 100 mm × 50 mm × 2 mm and 67 mm × 40 mm × 4 mm. From analysis obtained from one-way interaction approach, it was found that the shrinkage of mold cavity-I increased from 4.7 - 4.8% to 4.9 – 5.0% when the melt temperature was adjusted from 220ºC to 240ºC. The packing pressure effect on shrinkage was relatively small compared with melt temperature effect since it was not taken into account in static structural analysis. The two-way interaction approach result showed that the shrinkage was high at the center location of the plastic part. No shrinkage was recorded when the mass flow rate was high. At low injection mass flow rate (0.05 kg/s), the shrinkage improved with melt temperature. Shrinkage was 1 - 10% when melt temperature was 220ºC and shrinkage was 0 - 4.5% when melt temperature used was 240ºC. One-way interaction approach simulation for mold cavity-II was compared with physical result obtained from experimental study. Both simulation and the physical results showed almost the same flow speed, temperature and thickness. Recorded experimental flow speed was 0.05 - 0.1 s faster than the simulation. The average recorded temperature obtained from the experimental result was about 9ºC higher than the simulation. Simulation over predicted the plastic product of mold cavity-II shrinkage by 1 - 4.8%. Taguchi method and analysis of variance (ANOVA) were used to optimize the processing parameter for minimum shrinkage of mold cavity-II product. According to the statistical result, melt temperature, mold cooling time and injection speed were the significant factors. Due to the small dimension of the injection gate, the material in this region cooled down and solidified very fast to the extent that the applied packing pressure and packing time had no significant effect on adding material into the cavity to reduce product shrinkage during packing phase. As a result, these two parameters were not significant according to Taguchi and ANOVA analysis.